PENGGUNAAN MEDIA MESIN PEMBAGIAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI PEMBAGIAN PADA MATA PELAJARAN MATEMATIKA KELAS IV SDN 7 LIMBOTO - Langkadja, Mega Silvia; Fatimah Djafar; Febry Rizki Susanti Kalaka (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2025)
This research is motivated by the low learning outcomes of students in the Division material. This study aims to determine the improvement in the learning outcomes of fourth grade students of SDN 7 Limboto in the Division material in Mathematics. This type of research is classroom action research. The subjects of this study were 18 students of class IV SDN 7 Limboto. The data analysis techniques used in this study were analysis of test results and analysis of observation results. The results of this study indicate that the Application of Division Machine Media can improve student learning outcomes in the Division material. In cycle I, the learning outcomes of students who completed were 8 students 44.4% in the